1931
DOI: 10.1111/j.1151-2916.1931.tb16675.x
|View full text |Cite
|
Sign up to set email alerts
|

MECHANICAL AND THERMAL SHOCK TESTS ON CERAMIC INSULATING MATERIALS1

Abstract: Simple tests, as developed for daily production of electrical porcelain are given.Laboratory tests are described and results for a number of ceramic insulating materials are given. From these it is shown that mechanical strength and resistance to thermal shock are valuable indications of the mechanical properties of bodies and glazes. Results obtained in testing foreign-and American-made porcelains are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1936
1936
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sometimes the data were comparable and in other cases they were not. One study on porcelain [21] suggested round rod test data were superior, but this was probably due to the warpage of the rectangular specimens and the use of nonarticulating fixtures or due to intrinsic strength differences between the two specimen types. Cylindrical and square asfired reaction bonded silicon nitride specimens were tested for comparison by Newnham [22].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the data were comparable and in other cases they were not. One study on porcelain [21] suggested round rod test data were superior, but this was probably due to the warpage of the rectangular specimens and the use of nonarticulating fixtures or due to intrinsic strength differences between the two specimen types. Cylindrical and square asfired reaction bonded silicon nitride specimens were tested for comparison by Newnham [22].…”
Section: Introductionmentioning
confidence: 99%